Cell-based screen identifies porphyrins as FGFR3 activity inhibitors with therapeutic potential for achondroplasia and cancer - Yun-Wen Lin; Hsiao-Jung Kao; Wei-Ting Chen; Cheng-Fu Kao; Jer-Yuarn Wu; Yuan-Tsong Chen; Yi-Ching Lee (JCI Insight, 2023)
Overactive fibroblast growth factor receptor 3 (FGFR3) signaling drives pathogenesis in a variety of cancers and a spectrum of short-limbed bone dysplasias, including the most common form of human dwarfism, achondroplasia (ACH). Targeting FGFR3 activity holds great promise as a therapeutic approach for treatment of these diseases. Here, we established a receptor/adaptor translocation assay system that can specifically monitor FGFR3 activation, and we applied it to identify FGFR3 modulators from complex natural mixtures. An FGFR3-suppressing plant extract of Amaranthus viridis was identified from the screen, and 2 bioactive porphyrins, pheophorbide a (Pa) and pyropheophorbide a, were sequentially isolated from the extract and functionally characterized. Further analysis showed that Pa reduced excessive FGFR3 signaling by decreasing its half-life in FGFR3-overactivated multiple myeloma cells and chondrocytes. In an ex vivo culture system, Pa alleviated defective long bone growth in humanized ACH mice (FGFR3ACH mice). Overall, our study presents an approach to discovery and validation of plant extracts or drug candidates that target FGFR3 activation. The compounds identified by this approach may have applications as therapeutics for FGFR3-associated cancers and skeletal dysplasias.